Editorial: special issue on biochar as an option for sustainable resource management (EU COST Action TD1107 final publication). Issue 2 (3rd April 2017) - Glaser, Bruno; Baltrėnas, Pranas; Kammann, Claudia; Kern, Jürgen; Baltrėnaitė, Edita
Abstract: The articles appearing in this special issue on Biochar as an Option for Sustainable Resource Management are mainly the extended versions of the contributions presented in Biochar COST Action meetings, especially at the International Biochar conference held September 2015 at Geisenheim University (Germany), which was the final conference of the COST Action TD1107.